2006
DOI: 10.3354/meps311145
|View full text |Cite
|
Sign up to set email alerts
|

Determinism and plasticity of fish schooling behaviour as exemplified by the South Pacific jack mackerel Trachurus murphyi

Abstract: Pelagic fish schools are thought to show a general pattern of dispersion at night and aggregation within schools during the day. This pattern is often accepted as the major rule driving most of the other physiological, biological and ecological processes. Foraging on mobile prey, for instance, is assumed to be enhanced by schooling behaviour. Current theory assumes then that foraging is only possible for obligatory gregarious predatory fish from dawn to dusk. However, offshore mesopelagic communities perform v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…The classical view assuming that fish are scattering during the night and in schools during the day (see 'Introduction') has yet to be validated by in situ observations, taking into account that the irradiance level depends on school depth, water turbidity, lunar cycle, season and atmospheric conditions such as cloud coverage. The number of schools detected in our 2 study areas revealed an unusual pattern: fish schools were more numerous during the night than by day, although their internal fish school structure was less organised, as Bertrand et al (2006) observed for Trachurus murphyi off Peru. Feeding (Bertrand et al 2006), reproduction (Nøttestad et al 1996), migration (Fernoe et al 1998), the physiological condition of the fish, their intrinsic sensory perception (Partridge & Pitcher 1980, Bleckmann 1993) and the presence of predators (Massé et al 1996) have all been proposed to influence schooling behaviour (Brehmer 2004).…”
Section: Diel Schooling Dynamicsmentioning
confidence: 94%
See 2 more Smart Citations
“…The classical view assuming that fish are scattering during the night and in schools during the day (see 'Introduction') has yet to be validated by in situ observations, taking into account that the irradiance level depends on school depth, water turbidity, lunar cycle, season and atmospheric conditions such as cloud coverage. The number of schools detected in our 2 study areas revealed an unusual pattern: fish schools were more numerous during the night than by day, although their internal fish school structure was less organised, as Bertrand et al (2006) observed for Trachurus murphyi off Peru. Feeding (Bertrand et al 2006), reproduction (Nøttestad et al 1996), migration (Fernoe et al 1998), the physiological condition of the fish, their intrinsic sensory perception (Partridge & Pitcher 1980, Bleckmann 1993) and the presence of predators (Massé et al 1996) have all been proposed to influence schooling behaviour (Brehmer 2004).…”
Section: Diel Schooling Dynamicsmentioning
confidence: 94%
“…Moreover, no noticeable differences were found between the Venezuelan and Senegalese fish school descriptors, except for A min , a descriptor not characteristic of schooling behaviour. The higher A min values in Sénégal could reflect increased prey depth (Bertrand et al 2006) or the effect of local bottom depth configuration in our survey transects. The length of fish schools and its variability was always larger than school height in both populations.…”
Section: Schooling Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…"Patches" of high density can be related to larger abundance of prey, or to non-trophic characteristics. Therefore, knowledge of the diet and the plasticity of T. murphyi behaviour is important (see Konchina 1981;Konchina and Pavlov 1996;Bertrand et al 2004Bertrand et al , 2006). …”
Section: The Metapopulation Hypothesismentioning
confidence: 99%
“…Two of them, conditions 3 and 16, are actually in some way contradictory with Levin's definition. Indeed, the different populations cannot be considered as discrete and it is impossible to draw clear borders between them with the existing data (condition 16): T. murphyi has a high plasticity (Bertrand et al 2004(Bertrand et al , 2006, and can be encountered in the whole "Pacific belt". Condition 3 should also be discussed because we observed contradictory results: on the one hand, local differences occurred in the demographic structures but, on the other hand, there is not complete independence between the major dynamics of the different populations, as synchrony of variations in abundance, migrations, etc.…”
Section: Selection Of the Most Adapted Population Structurementioning
confidence: 99%